2023
DOI: 10.3390/foods12152919
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Antimicrobial Surveillance of Campylobacter Population in Italian Poultry

Francesca Marotta,
Anna Janowicz,
Romina Romantini
et al.

Abstract: Campylobacter is one of the most common foodborne diseases worldwide with increasing rates of antibiotic resistance. Most cases of campylobacteriosis can be traced back to the consumption of poultry meat. Despite many efforts to reduce contamination in farms and in slaughterhouses, the persistence of this pathogen in poultry products remains a problem. This study aimed to evaluate the genetic diversity and antibiotic resistance of 542 C. jejuni and C. coli in Italian poultry, in the framework of two National M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Antimicrobial resistance to aminoglycosides (gentamicin and streptomycin) was less frequent (5.4%), roughly similar to previous studies where the resistance to gentamicin and streptomycin was low (0.7% and 2.4% on average, respectively) in C. jejuni and C. coli isolates from human samples [ 13 , 14 ]. Conversely, we observed low rates of resistance to erythromycin (3.2%), another CIA, supporting previous data that indicated low resistance in C. jejuni from human and animal samples [ 12 , 13 , 14 ]. However, higher rates have been reported for C. coli isolates from human samples (8.5%), similar to our findings, and animals (range, 4.4% to 35.7%) [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Antimicrobial resistance to aminoglycosides (gentamicin and streptomycin) was less frequent (5.4%), roughly similar to previous studies where the resistance to gentamicin and streptomycin was low (0.7% and 2.4% on average, respectively) in C. jejuni and C. coli isolates from human samples [ 13 , 14 ]. Conversely, we observed low rates of resistance to erythromycin (3.2%), another CIA, supporting previous data that indicated low resistance in C. jejuni from human and animal samples [ 12 , 13 , 14 ]. However, higher rates have been reported for C. coli isolates from human samples (8.5%), similar to our findings, and animals (range, 4.4% to 35.7%) [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…The antimicrobial resistance of Campylobacter species has increased worldwide [ 12 ] largely due to antimicrobial overuse in humans and in food-producing animals. Certain antimicrobials have been used extensively to treat Campylobacter infection in humans.…”
Section: Introductionmentioning
confidence: 99%
“…These strains were isolated in different years, suggesting they did not originate from an outbreak but were potentially acquired from a common source. Recent studies have indicated that ST-2116 and ST-2863 are the most prevalent STs isolated from broilers in Italy, exhibiting genetic homogeneity ( Di Giannatale et al, 2019 ; Marotta et al, 2023 ). This suggests that human infections caused by these clones, which are extensively circulating in Italy, are likely linked to broilers and the consumption of contaminated poultry meat and related food products.…”
Section: Discussionmentioning
confidence: 99%